Comprehensive mapping of paediatric high grade glioma by oligo array comparative genomic hybridisation - Barrow, Jennifer H. (2011)
Overall paediatric high grade glioma (pHGG) has a poor prognosis, in part due to the lack of understanding of the underlying biology. We therefore used high resolution 244K oligo array comparative genomic hybridisation (oligo aCGH) (Agilent Technologies) to analyse DNA from 38 formalin-fixed paraffin embedded pHGG samples, including 13 DIPG. The pattern of gains and losses were distinct from those seen in HGG arising in adults. In particular we found 1q gain in 21% of our cohort compared to 9% in adults. Homozygous loss at 8p12 was seen in 6/38 (15%) of pHGG. This deletion has not been previously reported in adult or paediatric high grade gliomas. The minimal deleted region is of the gene ADAM3A and homozygous deletion of ADAM3A was confirmed by quantitative real time PCR (qPCR). This novel homozygous deletion of ADAM3A in pHGG merits further study. Amplification of the 4q11-13 region was detected in 8% of cases and included PDGFRA and KIT and subsequent qPCR analysis was consistent with amplification of PDGFRA. MYCN amplification was seen in 2/38 samples (5%) and was shown to be significantly associated with anaplastic astrocytomas (p=0.03). Loss of CDKN2A/B was seen in 4/38 (10%) samples by oligo a CGH, confirmed by FISH on TMAs, and was restricted to supratentorial tumours. ~50% of supratentorial tumours were positive for CDKN2B expression by IHC, whilst ~75% of brainstem gliomas were positive for CDKN2B expression (p = 0.03). Overall DIPG shared a similar spectrum of changes to supratentorial HGG with some notable differences including high frequency of 17p loss and 14q loss, low occurrence of 10q loss and lack of CDKN2A/B deletion.